Non-Muslim Community Resistance to Worship House Regulations in Sanggaberu, Aceh Singkil - Mardayanti, Lisa; Fajarni, Suci; Majid, Abdul (Department of Anthropology, 2025)
The establishment of houses of worship in Aceh Singkil exposes persistent tensions between religious freedom and diversity governance rooted in local regulations. This study analyzes the resistance strategies of the non-Muslim community in Sanggaberu to establish the GKPPD church and assesses how Aceh Qanun No. 4/2016 and Governor Regulation No. 25/2007 operate in practice. Adopting a qualitative single-case design with observation, in-depth interviews, and document review, purposively selected informants (non-Muslim leaders, Muslim leaders, and residents) were thematically analyzed. Findings indicate that complex licensing requirements—thresholds of users/supporters and multilayered recommendations—intertwine with majority social resistance, producing delays and failed permits despite formal compliance. In response, the community deploys three non-confrontational strategies: legal-advocacy through official licensing channels and legal consultation; socio-cultural dialogue and deliberation across faiths; and internal solidarity and spiritual reinforcement via rotational worship in temporary tents to sustain religious practice and cohesion. The gap between administrative compliance and social reality enables policy to function as an instrument of majority domination; therefore, more transparent and inclusive governance, alongside strengthened mediation capacities of FKUB and village authorities, is essential for harmonization. Abstrak: Pendirian rumah ibadah di Aceh Singkil menyingkap ketegangan antara kebebasan beragama dan tata kelola keberagaman yang berlandaskan regulasi lokal. Studi ini menganalisis strategi resistensi komunitas non-Muslim di Sanggaberu untuk mendirikan GKPPD serta memeriksa bagaimana Qanun Aceh No. 4/2016 dan Pergub NAD No. 25/2007 bekerja pada aras praktik. Menggunakan pendekatan kualitatif studi kasus melalui observasi, wawancara mendalam, dan telaah dokumen, informan dipilih secara purposif (pemuka non-Muslim, pemuka Muslim, dan warga), lalu data dianalisis secara tematik. Hasil menunjukkan bahwa kerumitan perizinan—ambang jumlah pengguna/pendukung dan rekomendasi berlapis—berkelindan dengan resistensi sosial mayoritas, sehingga memicu penundaan bahkan kegagalan izin meski persyaratan formal dipenuhi. Menjawab kondisi ini, komunitas menggerakkan tiga strategi non-konfrontatif: jalur legal-advokasi melalui kanal perizinan dan konsultasi hukum; pendekatan sosio-kultural berbasis dialog dan musyawarah lintas iman; serta penguatan solidaritas dan spiritualitas internal melalui ibadah bergilir di tenda darurat untuk menjaga kohesi dan keberlanjutan praktik keagamaan. Kesenjangan antara kepatuhan administratif dan realitas sosial membuat kebijakan mudah berfungsi sebagai instrumen dominasi mayoritas; karena itu, tata kelola yang lebih transparan, inklusif, dan berbasis keadilan substantif, berikut penguatan kapasitas mediasi FKUB dan otoritas desa, menjadi prasyarat harmonisasi.